An experimental investigation on the influence of port injection at valve on combustion and emission characteristics of B5/biogas RCCI engine - Dalha, I.B. (MDPI AG, 2020)
High unburned hydrocarbon (UHC) and carbon monoxide (CO) emissions, on account of the premixed air-fuel mixture entering the crevices and pre-mature combustion, are setbacks to reactivity-controlled compression ignition (RCCI) combustion at a low load. The influence of direct-injected B5 and port injection of biogas at the intake valve was, experimentally, examined in the RCCI mode. The port injection at the valve was to elevate the temperature at low load and eliminate premixing for reduced pre-mature combustion and fuel entering the crevices. An advanced injection timing of 21Â° crank angle before top dead centre and fraction of 50 each of the fuels, were maintained at speeds of 1600, 1800 and 2000 rpm and varied the load from 4.5 to 6.5 bar indicated mean effective pressure (IMEP). The result shows slow combustion as the load increases with the highest indicated thermal efficiency of 36.33 at 5.5 bar IMEP. The carbon dioxide and nitrogen oxides emissions increased, but UHC emission decreased, significantly, as the load increases. However, CO emission rose from 4.5 to 5.5 bar IMEP, then reduced as the load increases. The use of these fuels and biogas injection at the valve were capable of averagely reducing the persistent challenge of the CO and UHC emissions, by 20.33 and 10 respectively, compared to the conventional premixed mode. Â© 2020 by the authors.